2018
DOI: 10.1017/s0143814x18000375
|View full text |Cite
|
Sign up to set email alerts
|

The importance of salience: public opinion and state policy action on climate change

Abstract: How does the salience of environmental issues influence climate policy adoption in the American states? This article considers how two aspects of public salience, issue problem status and issue attention, work with environmental interest group membership to influence climate policy adoption in the American states. We contribute to the theoretical development of issue salience and offer alternative measures that capture differences in salience across subnational units. We find evidence that states where climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 67 publications
3
67
0
1
Order By: Relevance
“…These elements are socially constructed and shift and change over time, with differing impacts on regulatory outcomes. Climate research has found that perceived scientific uncertainty can delay policy action while issue salience can spur regulatory development (Bromley‐Trujillo & Poe, 2020; Cann & Raymond, 2018); it is less clear whether these dynamics hold true in other areas of energy politics. Future studies should explore the interaction of scientific uncertainty and dread environmental risk across issue areas, examining similarities among fracking research, climate politics, and socio‐technology studies more broadly.…”
Section: Resultsmentioning
confidence: 99%
“…These elements are socially constructed and shift and change over time, with differing impacts on regulatory outcomes. Climate research has found that perceived scientific uncertainty can delay policy action while issue salience can spur regulatory development (Bromley‐Trujillo & Poe, 2020; Cann & Raymond, 2018); it is less clear whether these dynamics hold true in other areas of energy politics. Future studies should explore the interaction of scientific uncertainty and dread environmental risk across issue areas, examining similarities among fracking research, climate politics, and socio‐technology studies more broadly.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, increasing population, rising emissions, and climate vulnerability make global warming a salient issue for urban America. Lastly, the U.S. federal government's lack of action on climate change [8][9][10][11] has provided a vacuum and policy opportunity for sub-national governments (including state and local governments) to play an important role in climate mitigation and adaptation [12,13]. States and cities are often left with large amounts of discretion to address this policy challenge as they see fit [14].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective remote sensing this result has some bias due to consideration of only non-cloudy observations. A known limitation is that compared to surveys which provide a direct indication of public concern based in individual response, internet search data can only provide active collective public response (Bromley-Trujillo, Poe, 2018), and by extension cannot inform individualistic inclinations that may govern the reason for concern. Further internet searches represents only active interest, so when air pollution may not be searched for on a clean air day, it si unclear whether perception regarding air pollution has changed.…”
Section: Discussionmentioning
confidence: 99%